5PSQ-100 Utility of social media as a source of paediatric drug safety, a systematic review. Issue 1 (23rd March 2023) - Vilimelis, I; Pérez-Ricart, A; Bosch Peligero, M; Calvo, A; Valls Sánchez, E; Codina-Jiménez, C; Marin, S; Suñé Negre, JM; Quiñones Ribas, C; Giménez-Juárez, JC
Abstract : Background and Importance: Paediatric population are predisposed to have more adverse drug reactions (ADR) and other drug related problems (DRP). Social media (SM) could be an innocuous source of pharmacovigilance. Aim and Objectives: Assess ADR and DRP evidence reported in SM. Material and Methods: A systematic review according PRISMA recommendations was conducted in MEDLINE, Embase and LILACS. Articles in English, Spanish and Catalan languages from inception up to September 2021 were reviewed using search terms related to paediatric age, SM and DRP. In the screening phase, articles not mentioning paediatrics and SM were excluded including grey literature. In the eligibility phase, articles related to non-pharmacological treatments/substances, surveys, recruitment protocols, sociological studies, professional use of SM and technological implementation were excluded. Articles including information about commonly used drugs in paediatrics were evaluated.Demographic variables, SM platforms, medicines and type of information (ADR, DRP or experiences and opinions (EO)) were analysed. Results: 6079 articles were assessed and 28 (0, 4%) met the inclusion criteria. 16 (57%) studies werequalitative, 6 (21%) quantitative and qualitative and quantitative 6 (21%). When mentioned, most articles analysed data from parents/caregivers (10;36%) and adolescents (2;7%). Gender of SM userwas not systematically reported but females were reported in 7 (25%) articles in a range in of 22-77%, in an article 245 females compared to 74 males and one referred that posts were mostly from mothers of young children. Most articles included data from forums (13;46%), Twitter (5;18%) and Facebook (6;21%). 17 (61%) reported information about vaccines, 3 (11%) asthma medications and 8 (28%) other medicines.8 articles (28%) reported an ADR including tremor, auto-injector wounds and vaccine ADR. Only in one article the severity was reported. EO were reported in 25 (89%) studies and 10 (36%) articles mentioned a DRP. Studies reported lack of adherence (4;14%), difficulties (3;11%) or doubts (2;7%) about drug administration of asthma inhalers (2;7%), epinephrine auto-injector (1;4%), antibiotics (1;4%), oral drugs (1;4%), ophthalmic drugs (1;4%) and topical drugs (1;4%). Conclusion and Relevance: Articles evaluating pharmacological drugs in paediatrics focused mostly on EO and scarce data about ADR and DRP were mentioned in SM. Consequently, more studies are required to take advantage from SM as a potential tool in paediatric pharmacovigilance. References and/or Acknowledgements: Conflict of Interest: No conflict of interest